Analisis Potensi Toleransi Varietas Padi (Oryza Sativa L.) Indonesia dan Vietnam Terhadap Cekaman Salinitas - Wulandari, Putri; Candra, Ifan Aulia (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
Global climate change is causing increased seawater intrusion into coastal areas, triggering soil salinity that has a serious impact on the productivity of food crops, especially rice. This study aims to examine and compare the resilience of local rice varieties in Indonesia and Vietnam to salinity stress through a systematic literature review approach. The literature was collected from Google Scholar, Scopus, and ScienceDirect databases, with a range of 2010–2023, and analyzed using narrative synthesis and thematical-comparative analysis. The results of the study showed that varieties such as Sigambiri Merah, Inpago-8, and Ramos in Indonesia, as well as OM567, OM5451, and OM6976 in Vietnam have different levels of tolerance to salinity. The difference is determined by the expression of genes such as HKT1; 5, Saltol, OsMYB2, and OsNAC6, which play a role in the mechanism of ion exclusion, osmolite accumulation, as well as increased antioxidant activity. Marker-based breeding approaches and CRISPR/Cas9 technology have also strengthened the genetic resilience of plants. This study recommends the integration of molecular and agronomic approaches in the development of superior varieties to support food security in salinity-affected lands in Southeast Asia.